2019
DOI: 10.3847/1538-4357/ab1648
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic Particle-in-cell Simulations of the Cosmic-Ray Streaming Instability: Linear Growth and Quasi-linear Evolution

Abstract: The gyro-resonant cosmic-ray (CR) streaming instability is believed to play a crucial role in CR transport, leading to growth of Alfvén waves at small scales that scatter CRs, and impacts the interaction of CRs with the ISM on large scales. However, extreme scale separation (λ pc), low cosmic ray number density (n CR /n ISM ∼ 10 −9 ), and weak CR anisotropy (∼ v A /c) pose strong challenges for proper numerical studies of this instability on a microphysical level. Employing the recently developed magnetohydrod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 82 publications
1
57
0
Order By: Relevance
“…Riquelme & Spitkovsky 2009;Ohira et al 2009) and the amplitudes predicted here are generally modest (for diffusivityκ29, the gyro-resonant |δB[rL]|/|B| ∼ 3 × 10 −4 (γL/BµGκ29) 1/2 ); however, two recent works studying the saturation of the gyro-resonant instability using the PIC method suggest possible ways that the effective ν might be lower than the QLT prediction. First, Bai et al (2019) find that the time required for the CR distribution to become fully isotropic in the Alfvén-wave frame is much longer than predicted by the QLT estimate. This behaviour arises because of particularly inefficient scattering across the zero pitch angle (µ = 0) barrier, which is both slow and requires scatterers of very short wavelength compared to rL (Völk 1973).…”
Section: Possible Resolutionsmentioning
confidence: 88%
See 2 more Smart Citations
“…Riquelme & Spitkovsky 2009;Ohira et al 2009) and the amplitudes predicted here are generally modest (for diffusivityκ29, the gyro-resonant |δB[rL]|/|B| ∼ 3 × 10 −4 (γL/BµGκ29) 1/2 ); however, two recent works studying the saturation of the gyro-resonant instability using the PIC method suggest possible ways that the effective ν might be lower than the QLT prediction. First, Bai et al (2019) find that the time required for the CR distribution to become fully isotropic in the Alfvén-wave frame is much longer than predicted by the QLT estimate. This behaviour arises because of particularly inefficient scattering across the zero pitch angle (µ = 0) barrier, which is both slow and requires scatterers of very short wavelength compared to rL (Völk 1973).…”
Section: Possible Resolutionsmentioning
confidence: 88%
“…(2) Analytic and numerical work explicitly following transport and scattering of CRs on "micro-scales" (e.g. Bai et al 2015Bai et al , 2019Lazarian 2016;Holcomb & Spitkovsky 2019;van Marle et al 2019), coupled to improved intermediate-scale "effective fluid" theories (e.g. Zank 2014;Zweibel 2017;Thomas & Pfrommer 2018), has begun to yield more detailed prescriptions for the "effective" transport coefficients of CRs as a function of local plasma properties (appropriate on scales much larger than the CR gyro-radius, but much smaller than the scales of e.g.…”
Section: Name Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…If CR-produced ionisation exceeds thermal ionisation (inner < 1 au) and/or ionisation produced by radionuclides (disc midplane), CRs will regulate the cycle of MRI activation and accretion (Offner et al, 2019). However, the coupling between the mean magnetic field and the CRs is also mediated by the degree of turbulence, which in turn is dictated by the MRI activity (Rodgers- Lee et al, 2017;Bai et al, 2019) -circumscribing a thoroughly non-linear problem.…”
Section: Impact Of Cosmic Rays On the Dynamical And Chemical Evolutiomentioning
confidence: 99%
“…Recent works have tackled the study of the nonresonant instability with PIC and hybrid simulations (e.g., Ohira et al 2009;Riquelme & Spitkovsky 2009;Gargaté et al 2010) and of the resonant instability with PIC and PIC-MHD simulations (e.g. Bai et al 2019;Holcomb & Spitkovsky 2019;); these studies have generally found results consistent with theory for the fasting growing mode and corresponding growth rate for the linear phase. Nevertheless, the saturation of the CR streaming instability is a complex and non-linear physical phenomenon that is not yet completely understood.…”
Section: Resonant and Non-resonant Streaming Instabilitymentioning
confidence: 99%